Are you Concerned? Patient Testimonials in Medical Communication Affect Healthy Recipients' Emotions and Memory - Sassenrath, Claudia; Greving, Hannah; Sassenberg, Kai (Frontiers in Communication, 2018)
Medical communication and health care intervention programs often include testimonials (i.e. an account of individuals’ experiences) when addressing health-related topics. Numerous findings provide evidence of the effectiveness of such testimonials on intentions for health behavior change. However, little is known about whether and how testimonials affect healthy lay people’s reception of health information (e.g., in journalistic reports about medical innovations). The present studies tested whether using patients versus doctors as testimonial protagonists in communication affects unconcerned recipients’ affective experiences and their memory performance regarding text content. Two experiments demonstrated that using patients as protagonists elicited stronger negative and weaker positive emotions in recipients than using doctors as protagonists. Results of one of the experiments further suggested that the affective experience influenced recipients’ memory performance so that less positive and more negative DBS-related information was remembered when patients were protagonists, due to elicited negative emotions. Implications for medical communication are discussed.